Inventions, public subsidies and market launch: opportunities and limits of patenting support in Argentina - Milesi, Dario; Aggio, Carlos; Verre, Vladimiro (Estudios de Economía, 2024)
ANR Patentes is an Argentinean program that gives grants for patents applications to innovative firms, entrepreneurs and researchers. Throughout the period 2007-2017, 83 projects (out of 195) were funded. Based on secondary sources and a survey conducted to beneficiaries, this study reconstructs the progress made by the patent applicants. The results show, on the one hand, that a high percentage of the patents have been granted, and, on the other hand, a group of projects are facing difficulties to reach the market. Thus, the study suggests the necessity to complement ANR Patentes with other instruments oriented to foster entrepreneurship and productive development.